(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This scientific article explores the significance of methodical competence in the professional development of education teachers. Methodical competence refers to the ability of teachers to effectively plan, organize, and deliver instruction using appropriate teaching methods and strategies. The article highlights the content areas of methodical competence and proposes strategies for its development. It emphasizes the importance of continuous professional development programs to enhance methodical competence and improve teaching quality in the field of education.